Resiliensi dan Burnout Akademik Mahasiswa Program Studi Bimbingan dan Konseling X - Danny Akbar; Slamat Fitriyadi; Insan Suwanto (Journal Innovation In Education, 2025)
This study aims to: 1) describe the resilience level of students in the Guidance and Counseling (BK) study program at  X; 2) describe the academic burnout level of students in the BK study program at  X. This study uses a quantitative approach with a population of all active students in the BK study program. The research sample consisted of 14 students from semester II to semester VIII. The data collection technique used an instrument in the form of a questionnaire consisting of a resilience scale and an academic burnout scale. The results of the study indicate that on average, students in the BK Study Program at  X have a high level of resilience. This finding is obtained from the average score of the resilience instrument that exceeds the cut-off/threshold of the CD-RISC or Resilience Scale, as well as the distribution of respondents who are mostly in the high resilience group. This condition indicates that students are relatively able to face academic pressure with a resilient, optimistic attitude, and are able to adapt to difficulties. This result indicates that resilience plays an important role in maintaining students' psychological well-being. Furthermore, the results of the study also show the distribution of academic burnout levels. Of the total respondents, 4 (25%) were in the low category, 9 (56.25%) in the moderate category, and 1 (6.25%) in the high category. The majority of students fell into the moderate category, meaning they experienced moderate levels of burnout symptoms, such as emotional exhaustion, decreased motivation, and feelings of being overwhelmed by work, but had not yet reached the chronic stage. In other words, academic burnout among students is present, but mostly at a moderate level. Based on the research and analysis, it can be concluded that students in the Guidance and Counseling Study Program at  X have relatively high levels of resilience, while academic burnout levels tended to be in the moderate category, with a small percentage experiencing high levels.